2018
DOI: 10.1038/s41598-018-23564-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Urinary Activin A as a Novel Biomarker Reflecting the Severity of Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a common but complex condition that is associated with increased morbidity and mortality. In the present study, we examined whether urinary activin A, a member of the TGF-beta superfamily, is present in mice with ischemia-reperfusion injury and in humans with AKI, as well as its potential as a biomarker for AKI. Expression of activin A was markedly increased in ischemic mouse kidneys. In situ hybridization demonstrated that activin mRNA was expressed in tubular cells of ischemic ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
(35 reference statements)
1
27
0
Order By: Relevance
“…Several studies had shown increased serum activin A levels in cardiovascular disease. In patients with type 2 diabetes, serum activin A levels were associated with higher incidence of cardiovascular diseases 39,40 . A comprehensive study by Yndestad et al found increased serum activin A levels in patients with CHF, concluding that abundant activin A may contribute to the pathogenesis of myocardial remodeling 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had shown increased serum activin A levels in cardiovascular disease. In patients with type 2 diabetes, serum activin A levels were associated with higher incidence of cardiovascular diseases 39,40 . A comprehensive study by Yndestad et al found increased serum activin A levels in patients with CHF, concluding that abundant activin A may contribute to the pathogenesis of myocardial remodeling 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Scr is not a sensitive marker for early AKI event, and, therefore, the development of more sensitive, accurate, and cost-effective biomarker assays for clinical AKI assessment other than Scr analysis is crucial [26]. In addition to SCr, several urine biomarkers have emerged as more sensitive indicators for early detection of AKI, such as urine levels of kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), activin A, and insulin-like growth factor-binding protein 7 (IGFBP-7) [27][28][29][30]. Urine Biomarker [(Tissue inhibitor of metalloproteinases 2) TIMP-2] × [IGFBP-7] level has also been proposed as a promising indicator for clinical AKI risk assessment [31].…”
Section: Introductionmentioning
confidence: 99%
“…In the kidney, activin A is expressed during embryonic development but not in maturity 16–18. However, activin A becomes abundantly expressed in the injured kidney in experimental models of acute kidney injury (AKI),19 20 glomerulonephritis and CKD 21–23. Circulating activin A levels doubled in unilateral ureter obstruction (UUO) rats while levels remained unchanged in unilateral nephrectomized controls with similar kidney function, suggesting the obstructed kidney as the source 24.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating activin A levels doubled in unilateral ureter obstruction (UUO) rats while levels remained unchanged in unilateral nephrectomized controls with similar kidney function, suggesting the obstructed kidney as the source 24. Renal tubular cells release activin A, which acts as a paracrine factor that promotes fibroblast proliferation, contributing to kidney fibrosis and CKD progression 17 19 25. Beyond the kidney microenvironment, circulating activin A levels are 10-fold higher in a high fat-fed, lipoprotein receptor deficient (Ldlr –/– ) CKD mouse model and elevated fivefold in a mouse model of Alport syndrome compared with wild types 22.…”
Section: Introductionmentioning
confidence: 99%